Relationship marketing and its effects towards customers' satisfaction: a case study on Cari Sparepart Sdn. Bhd. / Khairol Azli Othman - Othman, Khairol Azli (Faculty of Business and Management, 2003)
Relationship marketing is an importance strategy to implement by the company in order to success in the market. Through relationship marketing, every company will create the total customers satisfaction in competing with their competitors, The relationship strategic becomes a heart of the company to get better profitability's and stronger sustainable competitive advantage. Building a good relationship with customers is necessary and should be one of the company's main goals , Relationship marketing allows the company to focus on quality, customer service and marketing in order to maintain and build up good relationship with their customers. The linkages between quality, customer service and marketing must be exploited to achieve total customer's satisfaction and long-term relationship.